Pyoderma Gangrenosum and Inflammatory Bowel Disease- Case Reports - Nkrumah, K.N.; Addo, H.A.; Tachi, K. (Ghana Medical Journal, 2005)
Two cases of ulcerative colitis preceded by pyoderma gangrenosum in two female patients are described. One patient developed leg ulcers, pre-sumed to be due to sickle cell disease; the other developed crops of ulcers all over the body for several years. These patients attended and were managed at the Medical and the Reconstructive Surgical Units of the Korle Bu Teaching Hospital. The unusual presentation of pyoderma gangreno-sum and the importance of diagnosing underlying probable inflammatory bowel disease is high-lighted.
Journal Article
Keywords: Pyoderma gangrenosum; inflammatory bowel disease; bloody diarrhoea; infliximab